EFFECTIVENESS OF A HEADS-UP ADAPTIVE LANE DEVIATION WARNING SYSTEM FOR MIDDLE-AGED & OLDER ADULTS - Aksan, Nazan (Proc Int Driv Symp Hum Factors Driv Assess Train Veh Des, 2015)
46 participants (24 younger and 22 older) completed at least one out of four simulated drives designed to test the effectiveness of an Adaptive Lane Deviation Warning (LDW) system, and they drove through both a warnings-on and warnings-off version of each drive. Findings showed that LDW was effective in reducing reaction time for lane deviation corrections for both older (by 1.2 seconds) and younger drivers (by 1.6 seconds). The older and younger drivers did not differ in correction RTs when the warnings were turned off. But older drivers showed slower correction RTs than younger drivers in the warning-on drives. The data indicate that these benefits were specific to LDW rather than general improvement in driving performance. Cognitive processing speed emerged as a particularly robust predictor of benefits from the LDW compared to other domains of cognitive function.